O-GlcNAc transferase in astrocytes modulates depression-related stress susceptibility through glutamatergic synaptic transmission - Jun Fan; Fang Guo; Ran Mo; Liang-Yu Chen; Jia-Wen Mo; Cheng-Lin Lu; Jing Ren; Qiu-Ling Zhong; Xiao-Jing Kuang; You-Lu Wen; Ting-Ting Gu; Jin-Ming Liu; et al. (The Journal of Clinical Investigation, 2023)
Major depressive disorder is a common and devastating psychiatric disease, and the prevalence and burden are substantially increasing worldwide. Multiple studies of depression patients have implicated glucose metabolic dysfunction in the pathophysiology of depression. However, the molecular mechanisms by which glucose and related metabolic pathways modulate depressive-like behaviors are largely uncharacterized. Uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) is a glucose metabolite with pivotal functions as a donor molecule for O-GlcNAcylation. O-GlcNAc transferase (OGT), a key enzyme in protein O-GlcNAcylation, catalyzes protein posttranslational modification by O-GlcNAc and acts as a stress sensor. Here, we show that Ogt mRNA was increased in depression patients and that astroglial OGT expression was specifically upregulated in the medial prefrontal cortex (mPFC) of susceptible mice after chronic social-defeat stress. The selective deletion of astrocytic OGT resulted in antidepressant-like effects, and moreover, astrocytic OGT in the mPFC bidirectionally regulated vulnerability to social stress. Furthermore, OGT modulated glutamatergic synaptic transmission through O-GlcNAcylation of glutamate transporter-1 (GLT-1) in astrocytes. OGT astrocyte–specific knockout preserved the neuronal morphology atrophy and Ca2+ activity deficits caused by chronic stress and resulted in antidepressant effects. Our study reveals that astrocytic OGT in the mPFC regulates depressive-like behaviors through the O-GlcNAcylation of GLT-1 and could be a potential target for antidepressants.